2017
DOI: 10.1038/onc.2017.80
|View full text |Cite
|
Sign up to set email alerts
|

SPOP regulates prostate epithelial cell proliferation and promotes ubiquitination and turnover of c-MYC oncoprotein

Abstract: The E3 ubiquitin ligase adaptor speckle-type POZ protein (SPOP) is frequently dysregulated in prostate adenocarcinoma (PC), via either somatic mutations or mRNA downregulation, suggesting an important tumor suppressor function. To examine its physiologic role in the prostate epithelium in vivo, we generated mice with prostate-specific biallelic ablation of Spop. These mice exhibited increased prostate mass, prostate epithelial cell proliferation, and expression of c-MYC protein compared to littermate controls,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
91
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(96 citation statements)
references
References 60 publications
5
91
0
Order By: Relevance
“…Turnover of MYC is regulated by multiple cancer-associated E3s and E3 complexes in a tissue-specific manner, including SCF–FBXW7 (REFS 134136), CRL3–potassium channel tetramerization domain-containing protein 2 (KCTD2) 137 , HUWE1 (REFS 138140), CRL3–SPOP 141 and SCF–SKP2 (REF. 142).…”
Section: Regulation Of Gene Expression By Ubiquitin Ligasesmentioning
confidence: 99%
See 3 more Smart Citations
“…Turnover of MYC is regulated by multiple cancer-associated E3s and E3 complexes in a tissue-specific manner, including SCF–FBXW7 (REFS 134136), CRL3–potassium channel tetramerization domain-containing protein 2 (KCTD2) 137 , HUWE1 (REFS 138140), CRL3–SPOP 141 and SCF–SKP2 (REF. 142).…”
Section: Regulation Of Gene Expression By Ubiquitin Ligasesmentioning
confidence: 99%
“…Finally, MYC has been identified as a CRL3–SPOP substrate in prostate epithelial cells 141 . SPOP mutations found in prostate and endometrial cancers are thought to disrupt substrate binding, suggesting that SPOP plays a tumour-suppressor role in these tissues 12,141,149 .…”
Section: Regulation Of Gene Expression By Ubiquitin Ligasesmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that SPOP mutations and ERG rearrangements are mutually exclusive in prostate cancer, suggesting that both alterations may represent alternative mechanisms resulting in the same oncogenic phenotype in neoplastic prostate cells . SPOP targets ERG, AR, and c‐myc among others, for ubiquitin‐proteasome system degradation and mutations are associated with an increase in the levels of its substrate protein . Different data based on clonality analysis and in the presence of SPOP mutations in high‐grade prostate PIN suggest that SPOP mutations could be also an early and recurrent event in prostate tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%